Dynamics of tin plasmoids and thermal shielding onset from a liquid metal CPS target using ITER intra-ELM energy-range H0/H0-H+ beams - A. de Castro; M. Reji; D. Tafalla; I. Voldiner; K.J. McCarthy; D. Alegre; E. Oyarzábal; the OLMAT Team (Nuclear Fusion)
Liquid-Metal (LM) divertor configurations are being explored to identify potential solutions to develop more resilient Plasma Facing Components for harsh environments characterized by nominal and transient power loads that can seriously compromise the feasibility of conventional tungsten elements. In this work, tin (Sn) plasmoids generated in front of a LM filled Capillary Porous System target exposed to ITER-Intra edge localized mode (ELM) energy range (20–33 keV) particle beams (H ^0 and H ^0 -H ^+ mixtures), are investigated at the OLMAT High-Heat Flux facility. Local characterization of plasmoids, including absolute quantification of the ionic species densities and their non-stationary evolution with target surface temperature, are conducted using a novel configuration consisting of a single Langmuir Probe (LP) directly embedded in the target while also employing a solid Titanium-Zirconium-Molybdenum alloy target for LP measurement benchmarking. Optical Emission Spectroscopy provides additional plasma characterization while infrared pyrometry monitors target thermal response. The temporal dynamic evolution of Sn plasmoids is described by four phases that depend on target temperature, parameter that determine the net eroded Sn flux and eventually Sn plasma content and global plasma build-up. The final phase, initiated at target temperature of 1600 K, is associated with the first stages of a thermal shielding state with partial mitigation of incoming heat fluxes. The thermal shielding and heat-flux mitigation fraction characteristics are inferred by studying deviations of target thermal response against a simple 1-D heat conduction model. Finally, the main Sn erosion mechanisms (thermal sputtering and evaporation) and atomic collisional processes (charge-exchange, electron/high-energy neutral-ion impact and recombination processes of Sn atoms) involving keV-range energy particles (neutrals, protons) as contributions to plasma build-up and heat flux mitigation characteristics are considered, these being questions of importance when considering detached LM divertor configurations operating in ELM-containing regimes.